2014
DOI: 10.1371/journal.pone.0104629
|View full text |Cite
|
Sign up to set email alerts
|

Sex Determination in Highly Fragmented Human DNA by High-Resolution Melting (HRM) Analysis

Abstract: Sex identification in ancient human remains is a common problem especially if the skeletons are sub-adult, incomplete or damaged. In this paper we propose a new method to identify sex, based on real-time PCR amplification of small fragments (61 and 64 bp) of the third exon within the amelogenin gene covering a 3-bp deletion on the AMELX-allele, followed by a High Resolution Melting analysis (HRM). HRM is based on the melting curves of amplified fragments. The amelogenin gene is located on both chromosomes X an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 88 publications
1
22
0
Order By: Relevance
“…Like GC‐MS methods, DNA quantitation methods using PCR are widely used with high confidence. Although not widely adopted by crime labs as GC‐MS, several studies have reported new PCR HRM assays for forensic use for human STR and mitochondrial DNA typing, sex determination, DNA quantitation, body fluid analysis, blowfly species identification, and plant drug identification . In summary, this real‐time PCR HRM assay could be used to rapidly detect and identify Psilocybe species DNA even if it is comingled with human and/or marijuana DNA in a trace or degraded sample such as saliva or material recovered from drug paraphernalia.…”
Section: Discussionmentioning
confidence: 99%
“…Like GC‐MS methods, DNA quantitation methods using PCR are widely used with high confidence. Although not widely adopted by crime labs as GC‐MS, several studies have reported new PCR HRM assays for forensic use for human STR and mitochondrial DNA typing, sex determination, DNA quantitation, body fluid analysis, blowfly species identification, and plant drug identification . In summary, this real‐time PCR HRM assay could be used to rapidly detect and identify Psilocybe species DNA even if it is comingled with human and/or marijuana DNA in a trace or degraded sample such as saliva or material recovered from drug paraphernalia.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous miniature vessels with galena, cinnabar, jarosite, and hematite pigments, as well as resins and oils, were found with them (46,47), together with discs and other geometric shapes made from mica (a raw material strictly controlled by the ruling elite) (51), as well as orange lacquer negative-painted bowls from the Mixtequilla region in Veracruz (19,43). The diet of these individuals displayed a substantial marine component (53,54) although they came from the corridor leading to the Gulf Coast rather than the coast itself (19,27,28,30,31,51,53,54).…”
Section: The Multiethnic Population Of Teopancazcomentioning
confidence: 99%
“…There were three principal settlement pat-terns in Teotihuacan: the Pre-Classic period (Patlachique phase), from 400 to 100 BC approximately; the Middle Horizon (Tlamimilolpa, Xolalpan, and Metepec phases), from 300 to 650 AC; and the Coyotlatelco phase, from 700 to 900 AC (Parsons, 1987;Manzanilla, 2014). Towards the late Metepec and Coyotlatelco phases, changes in ceramics represented a break in the ceramic tradition compared with early Teotihuacan (1-200 AC), which Rattray describes as catastrophic (Rattray, 1987a).…”
mentioning
confidence: 99%
“…The first human occupation of the Teotihuacan Valley began in the late Pre-Classic period (400-100 BC), when inhabitants of the valley lived from the natural resources, such as corn and other plants and their derivatives, found in the surrounding areas of the San Juan river (Manzanilla, 2014). Archaeological analysis has shown cultural growth, with compounds of monumental architecture in the center, and groups of residential structures placed around them.…”
mentioning
confidence: 99%
See 1 more Smart Citation